2020
DOI: 10.1101/2020.10.22.350827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the Agonist Binding Mechanism to the Adenosine A1 Receptor

Abstract: Despite being amongst the most characterized G protein-coupled receptors (GPCRs), adenosine receptors (ARs) have always been a difficult target in drug design. To date, no agonist other than the natural effector and the diagnostic regadenoson has been approved for human use. Recently, the structure of the adenosine A1 receptor (A1R) was determined in the active, Gi protein complexed state; this has important repercussions for structure-based drug design. Here, we employed supervised molecular dynamics simulati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…The reason for this could be the divergent amino acid composition of the extracellular loops between hA 1 R and rA 1 R, which would favor different binding paths to the orthosteric site. 24 Overall, the compounds displayed a very similar binding profile across the human and rat A 1 R, suggesting that further studies in rats would be highly relevant for the potential use of the compounds in humans. The adenosine and NECA-derived analog pairs also display very similar affinities for both human and rat A 1 R, suggesting that it is the R 2 substituent on the phenoxy or benzyloxy ring that is key in determining the compound affinity for A 1 R. At the hA 1 R, the compounds with the highest affinity are 27−29, 49, 51, 53, and 54.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 82%
See 3 more Smart Citations
“…The reason for this could be the divergent amino acid composition of the extracellular loops between hA 1 R and rA 1 R, which would favor different binding paths to the orthosteric site. 24 Overall, the compounds displayed a very similar binding profile across the human and rat A 1 R, suggesting that further studies in rats would be highly relevant for the potential use of the compounds in humans. The adenosine and NECA-derived analog pairs also display very similar affinities for both human and rat A 1 R, suggesting that it is the R 2 substituent on the phenoxy or benzyloxy ring that is key in determining the compound affinity for A 1 R. At the hA 1 R, the compounds with the highest affinity are 27−29, 49, 51, 53, and 54.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 82%
“…BnOCPA has previously been identified as a high-potency A 1 R-selective full agonist. 13,22 Using insights from BnOCPA MD simulations 22,24 and with the aim of further improving the A 1 R selectivity and potency, we designed extended BnOCPA derivatives 15−18. Their binding and activity at human A 1 R (hA 1 R) were then explored using both a NanoBRET binding assay and a cAMP accumulation assay, respectively (Table 1).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand the unusual signalling properties of BnOCPA and the highly specific Gα coupling to Gob, we carried out dynamic docking simulations to study the basic orthosteric binding mode of BnOCPA in an explicit, fully flexible environment using the active cryo-EM structure of the A 1 R (PDB code 6D9H; Supplementary Movie 1). We previously reported that modifications at position N 6 of the adenine scaffold modulated the agonist binding path to A 1 R 69 . More precisely, N 6 -cyclopentyl analogues (CPA and HOCPA) markedly interact with the extracellular loop 2 (ECL2) compared to adenosine, while BnOCPA (which bears the N 6 -cyclopentyl-2-benzyloxy group) is most prone to engage residues of the A 1 R located at the top of transmembrane helix 1 (TM1) and TM7.…”
Section: Resultsmentioning
confidence: 99%